Rheological investigation of supramolecular physical gels in water/dimethylsulfoxide mixtures by lysine derivatives. Issue 3 (23rd January 2021) - Rangel Euzcateguy, Géraldine; Parajua‐Sejil, Caroline; Marchal, Philippe; Chapron, David; Averlant‐Petit, Marie‐Christine; Stefan, Loïc; Pickaert, Guillaume; Durand, Alain
Abstract: Two derivatives of lysine were synthesized by acylating the Nα with dodecanoic acid starting from commercial precursors in which the Nε was already acylated by the benzoyloxycarbonyl or o ‐chloro‐benzoyloxycarbonyl group. Both derivatives self‐assembled in dimethylsulfoxide/water mixtures (above 40% v/v water) leading to solid‐like formulations. The rheological properties were studied as a function of gelator concentration and solvent composition. From stress sweep experiments it was assumed that the gels consisted of jammed suspensions of mesoscopic clusters formed by self‐assembly processes similar to those at the origin of crystallization. The temporal variation of storage and loss moduli was monitored immediately after mixing over times between 20 and 120 min using isothermal oscillatory rheological experiments. Experimental curves were satisfactorily depicted using previously reported semi‐empirical equations. Both transient evolution and stationary values were consistent with the representation of gels as resulting from the formation, one‐dimensional growth and dynamic arrest of fractal clusters (with fractal dimension between 1.6 and 2.0). The presence of a chlorine atom within the aromatic ring of one of the lysine derivatives induced a significant increase of the gelation time scale and a decrease of rheological moduli. © 2021 Society of Chemical Industry Abstract : Transient and stationary rheological properties of supramolecular gels formed by lysine derivatives in water/dimethylsulfoxide mixtures were investigated. The model of jammed suspension of fibre‐like fractal clusters was proposed.